Hubungan Antara Lama Menstruasi Dengan Kadar Hemoglobin Pada Mahasiswi Fakultas Kedokteran Universitas Muslim Indonesia Angkatan 2016 - Dahlia, Dahlia; Rasfayanah, Rasfayanah; Dewi, Citra; Yusriani, Yusriani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Hemoglobin is an important component in the blood. If the blood lacks hemoglobin or the amount of hemoglobin in the blood is less than the normal amount, then the body will have anemia. The purpose of this study was to determine the relationship between menstrual periods with hemoglobin levels in female students. This research is a descriptive analytic research, cross-sectional approach, using total sampling technique. Sample amounted to 99 people in Faculty of Medicine UMI. Data collection was done by using questionnaire and measuring respondent hemoglobin. Data analysis using spearman test. There were 49 female students (49.5%) who had normal menstrual period with normal hemoglobin level (â‰¥12). There were 38 female (38.4%) students who had normal menstrual period with low hemoglobin level (< 12), there were three female students (3.0%) who had hypermenorrhoea or abnormal menstrual periods with normal hemoglobin (â‰¥12), and 9 9.1% women who had abnormal menstruation (hypermorrhoea) with hemoglobin low (<12), and no female students had hypomenorrhoea. Based on result of analysis of test of relationship obtained value p = 0,042 (smaller than value Î± = 0,05). The conclusion that can be taken is there is a significant relationship between the length of menstruation with hemoglobin level in student of Faculty of Medicine UMI bacth 2016.